Working capital management: a contribution to the furniture MPEs of Cláudio, MG (Research, Society and Development, 2018)
Working capital is a necessary financial resource to support the operational activities of a company, such as financing sales in installments, maintaining adequate inventory levels, paying suppliers, taxes, salaries, in addition to other expenses and operating costs. The inadequate management of this capital exposes the organization to several risks, among them the absence of liquidity and a fall in profitability, which may compromise its sustainability. Thus, this research is concerned with describing the factors that most influence the working capital management of micro and small enterprises in the furniture sector of Cláudio, MG. To reach this objective, a descriptive and exploratory research was carried out with a quantitative and qualitative approach. The data collection instrument was a questionnaire applied to an intentional sample of 7 furniture micro and small enterprises from Cláudio, MG. After analyzing the data, it was concluded that most of the companies surveyed neither knew nor used in a systematized manner all the necessary tools for efficient working capital management.